P53 suppresses the progression of hepatocellular carcinoma via miR‐15a by decreasing OGT expression and EZH2 stabilization. Issue 19 (12th September 2021) - You, Zhenyu; Peng, Dandan; Cao, Yixin; Zhu, Yuanzhe; Yin, Jianjun; Zhang, Guangxing; Peng, Xiaodong
Abstract: Existing literature has highlighted the tumour suppressive capacity of microRNA‐15a (miR‐15a); however, its role in hepatocellular carcinoma (HCC) remains relatively unknown. This study aimed to investigate the role of miR‐15a in HCC and the associated underlying mechanism. Initially, RT‐qPCR was performed to detect the expression of miR‐15a in HCC tissues and cells. Bioinformatics analysis, Pearson correlation coefficient, dual‐luciferase reporter assay, and molecular approaches were all conducted to ascertain the interaction between miR‐15a and O‐linked N‐acetylglucosamine (GlcNAc) transferase (OGT). PUGNAc treatment and cycloheximide (CHX) assay were performed to evaluate O‐GlcNAc and the stabilization of the enhancer of zeste homolog 2 (EZH2). Finally, gain‐ and loss‐of‐function studies were employed to elucidate the role of P53 and the miR‐15a/OGT/EZH2 axis in the progression of HCC, followed by in vivo experiments based on tumour‐bearing nude mice. Our results demonstrated that the miR‐15a expression was decreased in the HCC tissues and cells. P53 upregulated miR‐15a expression, which inhibited the proliferation, migration and invasion of HCC cells, while inducing apoptosis and triggering a G0/G1 cell cycle phase arrest. OGT stabilized EZH2 via catalysing O‐GlcNAc, which reversed the effect of P53 and miR‐15a. The results of our in vivo study provided evidence demonstrating that P53 could suppress the development of HCC via the miR‐15a/OGT/EZH2 axis. P53 was found to inhibit the OGT expression by promoting the expression of miR‐15a, which destabilized EZH2 and suppressed the development of HCC. The key findings of our study highlight a promising novel therapeutic strategy for the treatment of HCC.